2018
DOI: 10.1016/j.ynstr.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated DNA methylation aging and increased resilience in veterans: The biological cost for soldiering on

Abstract: Accelerated epigenetic aging, the difference between the DNA methylation-predicted age (DNAm age) and the chronological age, is associated with a myriad of diseases. This study investigates the relationship between epigenetic aging and risk and protective factors of PTSD. Genome-wide DNA methylation analysis was performed in 211 individuals including combat-exposed Australian veterans (discovery cohort, n = 96 males) and trauma-exposed civilian males from the Grady Trauma Project (replication cohort, n = 115 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 65 publications
2
34
2
Order By: Relevance
“…Van Zuiden and colleagues () successfully created a diagnostic classifier containing three pretrauma variables: high GR numbers, high GILZ expression, and low FKBP5 expression. All of these findings are interesting in the context of a recent cross‐sectional study in which it was shown that gene expression changes observed cross‐sectionally in veterans (i.e., after trauma exposure) overlapped significantly with those observed before and after combat exposure in two independent replication samples, highlighting that these gene expression changes were modified postcombat (Mehta, Voisey, et al., ).…”
Section: Discussionmentioning
confidence: 69%
“…Van Zuiden and colleagues () successfully created a diagnostic classifier containing three pretrauma variables: high GR numbers, high GILZ expression, and low FKBP5 expression. All of these findings are interesting in the context of a recent cross‐sectional study in which it was shown that gene expression changes observed cross‐sectionally in veterans (i.e., after trauma exposure) overlapped significantly with those observed before and after combat exposure in two independent replication samples, highlighting that these gene expression changes were modified postcombat (Mehta, Voisey, et al., ).…”
Section: Discussionmentioning
confidence: 69%
“…Childhood trauma was examined in four studies, but only one of these reported a significant association with childhood sexual abuse (40), that was supported by the findings of the meta-analysis of three studies (33). Six studies investigated lifetime posttraumatic stress disorder in predominantly war veterans (33,49,61,(69)(70)(71). Four of these reported no association overall.…”
Section: Stress Posttraumatic Stress Disordermentioning
confidence: 85%
“…A number of studies combined data from multiple cohorts (27,32), including one meta-analysis (33). Even when excluding the meta-analysis (33), multiple cohorts were used in more than one study; Women's Health Initiative (WHI) Study (27,32,(34)(35)(36), Lothian Birth Cohort 1936 (LBC1936) (37-39), Medical Research Council (MRC) National Survey of Health & Development (NSHD) (32,40,41), The Parkinson's disease, Environment & Genes (PEG) study (27,32,42), Veterans Affairs Normative Aging Study (43,44), Adults in the Making Project (AIM) (45,46), Strong African American Healthy Adult Project (SHAPE) (45)(46)(47)(48), Grady Trauma Project (GTP) (49,50), Family and Community Health Study (FACHS) (30,51), Invecchiare nel Chianti (INC) (32,36), and the Epidemiological Investigations of the Changes of Preventing, Recognizing Early and Optimally Treating Chronic Diseases in an Elderly Population (ESTHER) cohort (52,53).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although understanding resilience is very important for understanding, preventing and treating PTSD (see Horn & Feder 2018) resilience as a research aim (see Mehta et al 2018) and treatment target has been largely neglected. Resilience does not mean just the absence of PTSD.…”
Section: Ptsd Between Resilience and Vulnerability/weaknessmentioning
confidence: 99%